Werner Herzog em busca da compreensão humana - Leão, Rita de Cássia da Silva (2015)
All movie-making has an anthropological character, as it is as open-ended as humankind itself. The works of Werner Herzog run parallel with fundamental anthropology, which seeks to understand the process of penetration of man into the world and the inseparable process of penetration of the world into man. The first movie that is analyzed, Wodaabe: Herdsman of the Sun, deals with love of beauty among beings who feel despised by neighboring peoples. The second, Grizzly Man, is about a man who wanted to be a bear, as he could not stand living among humans. The third, The Cave of Forgotten Dreams, tells us how humankind dreamed 32 thousand years ago; how it projected its double on cave walls and small statues. Paintings and statues feature at the same time a penchant for both the fantastic and the reality of shapes and forms. It is not Herzog´s movie settings or themes which are anthropological; it is his view of the world and his way of making movies, which transmutes real into imaginary, and imaginary into real